Introduction to nutrition informatics in Australia. Issue 4 (23rd October 2014) - Maunder, Kirsty; Williams, Peter; Walton, Karen; Ferguson, Maree; Beck, Eleanor; Probst, Yasmine
Abstract Aim The aim of this study was to provide an introduction to nutrition informatics, including a brief history and a rationale of its importance for Australian dietetics. Methods The study method used was a narrative review informed by a literature review and expert consultation with the Academy of Nutrition and Dietetics. Results Nutrition informatics has demonstrated potential to improve efficiencies, reduce costs, support research and ultimately enhance patient care. Governments and organisations have identified this as an emerging priority area. The Dietitians Association of Australia has launched initiatives to advocate and provide strategic advice on dietetic involvement in biomedical informatics and specifically nutrition informatics. Conclusions If nutrition standards and processes are not integrated into information systems, dietitians may inherit technologies that do not support dietetic work practices, and opportunities to enhance nutrition services may be missed. It is recommended that dietitians be aware of the opportunities and potential benefits of nutrition informatics, become familiar and involved in technology initiatives, and take the lead in guiding the development and implementation of technologies that may impact patient nutritional care.